Disaster resilience in transportation: Japan earthquake and tsunami 2011. Issue 4 (4th November 2014) - Nakanishi, Hitomi; Black, John; Matsuo, Kojiro
Abstract : Purpose: – The purpose of this paper is to examine the transportation organizational service provision and travel behavioral responses after the March 2011 disaster in North East Japan. This research aims to identify the areas for capacity building in transportation to support resilient built environments. Design/methodology/approach: – A case study approach was taken to examine the transportation organizational service provision in one of the most devastated communities after the 2011 Japanese earthquake and tsunami. Data on post-disaster transportation arrangements were collected from local newspapers, desk reviews of reports by transportation operators and the local council, semi-structured interviews with local council and community groups, and a residents' questionnaire surveying travel behavior. Organizational responses were analyzed by: the pre-disaster phase, the emergency phase, the rebuilding (temporary settlement) phase and the recovery (permanent settlement) phase. Findings: – Transportation demand changes dramatically in the emergency phase. In the re-building phase, an efficient and effective provision of a transportation service is required. The recovery and pre-disaster phases are critical as these are the time to build capacity for resilience. Practical application of the land use and transportation planning process is recommended in forming a transportation master plan. Originality/value: – This research is the first attempt to analyze the transportation organizational responses after a disaster in four discrete temporal dimensions. The knowledge provided in the paper is derived from the examination of the transportation responses in a city after a major disaster. The findings are more generally applicable to any built environments that are aiming for resilience.